Оцінка та прогнозування попиту на продукцію олійно-жирової галузі України - Жадан, Тетяна Андріївна (ВД "ІНЖЕК", 2014)
У статті проаналізовано динаміку та структуру споживання олійно-жирової продукції в Україні, рівень задоволення фізіологічних потреб населення в рослинній олії та жирах з використанням нормативного методу. Розглянуто сучасне тлумачення сутності економічної категорії "потреба" та запропоновано уточнене формулювання змісту категорії "потреба в рослинній олії та жирах". Висвітлено методику побудови прогнозного балансу попиту і пропозиції на олійно-жирову продукцію, ключовою складовою якого є внутрішній фонд споживання. За допомогою кореляційно-регресійного аналізу досліджено тісноту взаємозв'язку між обсягом фонду споживання рослинної олії та споживанням рослинної олії на душу населення, чисельністю населення України, що стало у підґрунті розробки системи економіко-математичних моделей для оцінки та прогнозування фонду споживання рослинної олії.

The article aims at assessing and forecasting of the demand for oil and fat products. Using the standard method, the dynamics and structure of consumption of fat-and-oil production in Ukraine were analyzed, as well as level of satisfaction of the consumers' physiological demand of vegetable oil and fats. A modern interpretation of the substance of economic category "demand" was considered and a revised wording of the category "demand for vegetable oil and fats" proposed. Highlighted is the methodology for making of the forecasting balance of supply and demand concerning oil and fat products, with domestic consumption fund as key component. Using the correlation and regression analysis, the closeness of relationships between the volume of vegetable oil fund and vegetable oil consumption per capita of the population of Ukraine were studied to form the basis for the development of economic-mathematical models for assessing and forecasting of vegetable oil consumption fund.
Assessment And Forecasting of Demand for the Products of Fat-and-Oil Industry in Ukraine
Keywords: попит; пропозиція; баланс попиту і пропозиції; фонд споживання; потреба; олійно-жирова галузь; demand; supply; balance of demand and supply; consumption fund; demand; fat-and-oil industry